Breast surgery and regional anaesthesia. Issue 1 (March 2019) - FitzGerald, Simon; Odor, Peter M.; Barron, Ann; Pawa, Amit
Abstract : Regional anaesthesia techniques are an important adjunct to perioperative care of breast surgery patients. This chapter focuses on the practical application, evidence base and advantages of peripheral nerve block regional anaesthesia in the anaesthetic management of patients undergoing breast surgery. Functional anatomy and fascial plane blocks are discussed alongside paravertebral and paraspinal techniques. Guidance on the performance the range of ultrasound-guided blocks is provided. The role that regional anaesthesia may have in reducing the risk of breast cancer recurrence following mastectomy surgery is explored.